"The Abomination of Desolation": Eastern Christian Apocalyptic Literature and the Symbolic Construction of Islam - Grypeou, Emmanouela (Collectanea Christiana orientalia, 2023)
This article focuses on the Christian apocalyptic literature that was produced as a specific reaction to the emergence of Islam and the consolidation of the Islamic rule in the Eastern provinces of Byzantium. The discussion examines how these texts re-cycled, used and manipulated long established cultural stereotypes, biblical exegetical topoi and traditional apocalyptic motifs in order to construct an image of the Muslims as the symbolic "Other".